Performance evaluation of a power tiller for soil tillage operation on various soil moisture contents of dry paddy field: a case study / Jairon Paulous - Paulous, Jairon (Faculty of Plantation and Agrotechnology, 2016)
Land preparation is a significant practice in rice cultivation. The creation of commodious machinery especially power tiller for land preparation proved that it can improve ploughing quality and increased grain yield, but not only that, it is also reduces elapsed time and the costs of land preparation. The study was conducted to test the relationship between soil moisture versus ploughing depth, speed versus ploughing depth, and effective field capacity (EFC) versus fuel consumption using power tiller that is Two-Wheel Tractor (2WT) (Model S120). The data are collected such as percentage of soil moisture in the morning, afternoon and evening, time taken by machine during ploughing operation, total time including turning time, fuel consumption, ploughing depth. Replication was made 6 times in different plot and different soil moisture. Replication was made 2 times in the morning, 2 times in the afternoon and 2 times in the evening. The results show that the soil moisture 11.38% in the morning, 8.33% in the afternoon and 6.53% in the evening. Higher the soil moisture will increase the average of ploughing depth. This study shows that the average speed of power tiller during ploughing operation are 1.0122, 1.0519, 1.088, 1.11 02, 1.1285 and 1.1329 km/hr respectively. The mean of ploughing depth for 30 random sample taken from each plot is 7.97 and 7.85cm (morning), 6.83 and 6.62cm (afternoon), 6.42 and 6.11 cm (evening). The effective field capacity for each plot is 0.047,0.048,0.048,0.049,0.050 and 0.050 halhr respectively. The fuel consumption recorded is 1.349, 1.386, 1.415, 1.467, 1.551, and 1.563 Llhr respectively. Higher EFC will increase the fuel consumptions.